Towards an Effective Synthesis of Difunctionalized Heptacyclo [6.6.0.02, 6.03, 13.04, 11.05, 9.010, 14]tetradecane: Ligand Effects on the Cage Assembly and Selective C−H Arylation Reactions. Issue 14 (1st June 2021) - Marset, Xavier; Recort‐Fornals, Martí; Kpante, Malkaye; Zieliński, Adam; Golz, Christopher; Wolf, Lawrence M.; Alcarazo, Manuel
Abstract: A series of strong π‐acceptor polyfluorinated and dicationic chelating phosphines have been synthesized and evaluated in the Rh‐catalysed dimerization of norbornadiene (NBD) into its thermodynamically more stable dimer, heptacyclo[6.6.0.0 2, 6 .0 3, 13 .0 4, 11 .0 5, 9 .0 10, 14 ] tetradecane (HCTD). While dicationic ligands direct the dimerization towards HCTD, by the use of neutral polyfluorinated ancillary ligands endo‐endo ‐heptacyclo [8.4.0.0 2, 12 .0 3, 8 .0 4, 6 .0 5, 9 .0 11, 13 ]tetradecane (BINOR−S) is selectively obtained. In addition, a selective Pd‐catalysed arylation at position C8 of the HCTD framework is achieved by the use of a picolylamide directing group previously attached at C1. Theoretical calculations have been performed to understand the origin of that regioselectivity. Abstract :